Ser não é tudo que se é: performances na literatura de Marcelino Freire. - Pinter, Kayanna (2013)
The literary narrative of Marcelino Freire, brazilian author known specially around the 90 s presents some performative ways. These performances are not present only in his narratives, surpassing the literary universe created by the author and putting themselves into the personas created by him to introduce his writing to the book publishing market and to the readers. It is from the perspective that the literary universe of Marcelino Freire develops itself in a performative and fragmented way that we developed this master s thesis, reflecting about how Marcelino Freire discusses the structure of the short stories and short-short stories, also problematizing the authorial and representational performances. Therefore, we used analytical references that emphasize the relation between literature and society, understanding the performance theories as a way that can explain the representation of the reality, what makes the narrative of the author not only a place of escape, but specially a place of reflection and comprehension of the manifestations of sexuality in contemporary society, mediated by the aesthetic arrangement of writing and the oral language used by his characters. The short stories and short-short stories of Freire, seen as mímesis de produção, move the reader and the literary criticism perspective, uniting author, literary narrative and reader.